Urinary extracellular vesicular release of aquaporins in patients with renal transplantation - Oshikawa-Hori, Sayaka (BMC Nephrol, 2019)
BACKGROUND: Diuresis has been observed within a week following renal transplantation, suggesting that the procedure causes acute disturbance of renal water homeostasis. Aquaporin (AQP) 1 and AQP2, important proteins for renal water reabsorption, have been identified in urinary extracellular vesicles (uEV-AQP1 and -AQP2), and experimental studies have shown that the presence of uEV-AQP1 and -AQP2 may be an indicator of their levels of expression in the kidney. However, the release patterns of uEV-AQP1 and -AQP2 during the acute phase following renal transplantation are largely unknown. METHODS: In this study, we examined the release of uEV-AQP1 and -AQP2 in recipients until 6 days (day 6) after renal transplantation. At Miyazaki prefectural Miyazaki Hospital, Japan, uEVs were obtained from 7 recipients, all of whom had received renal allografts from living donors. uEVs were isolated by differential centrifugation. RESULTS: Immunoblotting analysis showed that the release of uEV-AQP2 was significantly decreased on day 1 in comparison with a control sample (from 3 healthy volunteers), accompanied by high urine output and low urine osmolality. Thereafter, the level increased gradually to the control level by day 6. The release pattern of uEV-AQP1 was similar to that of uEV-AQP2, but the levels did not reach statistical significance in comparison with the control level at any of the time points examined. Evaluation of the relationship between urinary osmolality and uEV-AQPs revealed a significant correlation for uEV-AQP2, but not for uEV-AQP1. CONCLUSION: These results indicate that acute diuresis after renal transplantation might be due to a decrease in the renal expression of AQP2, whose level can be estimated from the amount released in uEVs.